Psychophysiological effects of music on acute recovery from high-intensity interval training - Jones, L.; Tiller, N. B.; Karageorghis, C. I. (Physiology & Behavior, 2017)
Numerous studies have examined the multifarious effects of music applied during exercise but few have assessed the efficacy of music as an aid to recovery. Music might facilitate physiological recovery via the entrainment of respiratory rhythms with music tempo. High-intensity exercise training is not typically associated with positive affective responses, and thus ways of assuaging negative affect warrant further exploration. This study assessed the psychophysiological effects of music on acute recovery and prevalence of entrainment in between bouts of high-intensity exercise. Thirteen male runners (Mage = 20.2 ± 1.9 years; BMI = 21.7 ± 1.7; V O2 max = 61.6 ± 6.1 mL·kg·min- 1) completed three exercise sessions comprising 5 × 5-min bouts of high-intensity intervals interspersed with 3-min periods of passive recovery. During recovery, participants were administered positively-valenced music of a slow-tempo (55-65 bpm), fast-tempo (125-135 bpm), or a no-music control. A range of measures including affective responses, RPE, cardiorespiratory indices (gas exchange and pulmonary ventilation), and music tempo-respiratory entrainment were recorded during exercise and recovery. Fast-tempo, positively-valenced music resulted in higher Feeling Scale scores throughout recovery periods (p < 0.01, p2 = 0.38). There were significant differences in HR during initial recovery periods (p < 0.05, p2 = 0.16), but no other music-moderated differences in cardiorespiratory responses. In conclusion, fast-tempo, positively-valenced music applied during recovery periods engenders a more pleasant experience. However, there is limited evidence that music expedites cardiorespiratory recovery in between bouts of high-intensity exercise. These findings have implications for athletic training strategies and individuals seeking to make high-intensity exercise sessions more pleasant.